2014 IEEE China Summit &Amp; International Conference on Signal and Information Processing (ChinaSIP) 2014
DOI: 10.1109/chinasip.2014.6889350
|View full text |Cite
|
Sign up to set email alerts
|

A novel radar radiation control strategy based on passive tracking in multiple aircraft platforms

Abstract: This paper proposes a radar radiation control method based on cooperation tracking of multiple sensors. The main idea of the method is passive tracking in multiple platforms is used preferentially, while radar tracks target timely according to the tracking accuracy. In this paper, a tracking accuracy metric called interactive multiple model predicted covariance (IMMPC) is derived by IMM-EKF algorithm. By comparing with the pre-defined threshold, whether or not the radar transmitter radiates energy is determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…On the other hand, in [28], only the minimization of total transmitted power for radar networks is considered. From the previous results in [26], [28], we can conclude that the revisit interval affects the target tracking accuracy, and the transmitted power affects the target detection performance during tracking process. Therefore, the LPI performance for target tracking in DRNS can be improved by jointly optimizing the radar revisit interval and the transmitted power for a predefined target tracking accuracy, where the fewer number of total radiation times and lower transmitted power leads to smaller transmission power consumption.…”
Section: Major Contributionsmentioning
confidence: 72%
See 3 more Smart Citations
“…On the other hand, in [28], only the minimization of total transmitted power for radar networks is considered. From the previous results in [26], [28], we can conclude that the revisit interval affects the target tracking accuracy, and the transmitted power affects the target detection performance during tracking process. Therefore, the LPI performance for target tracking in DRNS can be improved by jointly optimizing the radar revisit interval and the transmitted power for a predefined target tracking accuracy, where the fewer number of total radiation times and lower transmitted power leads to smaller transmission power consumption.…”
Section: Major Contributionsmentioning
confidence: 72%
“…Later, Zhang et al [25] developed an optimal sensor selection strategy based on passive sensor cooperation, and it was shown that the proposed algorithm can decrease the radar radiation times with excellent target tracking accuracy. Chen et al extended the results of the previous research and presented a radar radiation control strategy for multiple aircraft platforms based on time difference of arrival (TDOA) cooperation [26], which utilized the comparison of covariance and the predefined threshold to control the radiation state [27]. Overall speaking, the reported works verified that adaptive transmit parameters control was an effective technique to improve the LPI performance for radar systems.…”
Section: Background and Motivationmentioning
confidence: 88%
See 2 more Smart Citations
“…In Wang et al (), Wang et al propose a joint revisit and dwell time management strategy for single‐target tracking based on the predicted Bayesian Cramer‐Rao lower bound in‐phased‐array radar system, where the resource burden is minimized with the target‐tracking performance, meeting a specified threshold. Also, LPI‐based radar resource‐aware design for target tracking has been addressed in multiple‐target tracking (Zhang et al, ) and multisensor selection scenarios (J. Chen et al, ; Kalandros & Pao, ; Puranik & Tugnait, ).…”
Section: Introductionmentioning
confidence: 99%